Identifying the key concerns of Irish persons with intellectual disability - Garcia Iriarte, Edurne (My University, 2014)
Background: Internationally, people with intellectual disability are socially marginalized, and their rights under the United Nations Convention for the Rights of Persons with Disabilities (CRPD) are often ignored. Aims: This paper aims to define the key concerns of adults with an intellectual disability in relation to their participation in society using an inclusive research strategy for both data gathering and data analysis. Methods: A national study involving 23 focus groups and 168 persons was conducted on the island of Ireland with people with intellectual disability as co-facilitators. Findings: A thematic content analysis was undertaken of the verbatim transcripts initially by university co-researchers, and 19 themes were identified. Co-researchers with intellectual disability joined in identifying the eight core themes. These were as follows: living options, employment, relationships, citizenship, leisure time, money management, self-advocacy, and communication. Discussion: The concerns are discussed within the framework of the CRPD, and implications for transforming service policy are drawn.
PUBLISHED
Keywords: Inclusive research; Intellectual disability; Ireland; National survey; Inclusive Society; INCLUSION; INTELLECTUAL DISABILITY